Association of a schizophrenia-risk nonsynonymous variant with putamen volume in adolescents: a voxelwise and genome-wide association study - Luo, Qiang; Chen, Qiang; Wang, Wenjia; Desrivières, Sylvane; Quinlan, Erin Burke; Jia, Tianye; Macare, Christine; Robert, Gabriel H.; Cui, Jing; Guedj, Mickaël; Palaniyappan, Lena; Kherif, Ferath; et al. (JAMA psychiatry, 2019)
Importance Deviation from normal adolescent brain development precedes manifestations of many major psychiatric symptoms. Such altered developmental trajectories in adolescents may be linked to genetic risk for psychopathology. Objective To identify genetic variants associated with adolescent brain structure and explore psychopathologic relevance of such associations. Design, Setting, and Participants Voxelwise genome-wide association study in a cohort of healthy adolescents aged 14 years and validation of the findings using 4 independent samples across the life span with allele-specific expression analysis of top hits. Group comparison of the identified gene-brain association among patients with schizophrenia, unaffected siblings, and healthy control individuals. This was a population-based, multicenter study combined with a clinical sample that included participants from the IMAGEN cohort, Saguenay Youth Study, Three-City Study, and Lieber Institute for Brain Development sample cohorts and UK biobank who were assessed for both brain imaging and genetic sequencing. Clinical samples included patients with schizophrenia and unaffected siblings of patients from the Lieber Institute for Brain Development study. Data were analyzed between October 2015 and April 2018. Main Outcomes and Measures Gray matter volume was assessed by neuroimaging and genetic variants were genotyped by Illumina BeadChip. Results The discovery sample included 1721 adolescents (873 girls [50.7%]), with a mean (SD) age of 14.44 (0.41) years. The replication samples consisted of 8690 healthy adults (4497 women [51.8%]) from 4 independent studies across the life span. A nonsynonymous genetic variant (minor T allele of rs13107325 inSLC39A8, a gene implicated in schizophrenia) was associated with greater gray matter volume of the putamen (variance explained of 4.21% in the left hemisphere; 8.66; 95% CI, 6.59-10.81;P = 5.35 × 10−18; and 4.44% in the right hemisphere;t = 8.90; 95% CI, 6.75-11.19;P = 6.80 × 10−19) and also with a lower gene expression ofSLC39A8specifically in the putamen (t127 = −3.87;P = 1.70 × 10−4). The identified association was validated in samples across the life span but was significantly weakened in both patients with schizophrenia (z = −3.05;P = .002; n = 157) and unaffected siblings (z = −2.08;P = .04; n = 149). Conclusions and Relevance Our results show that a missense mutation in geneSLC39A8is associated with larger gray matter volume in the putamen and that this association is significantly weakened in schizophrenia. These results may suggest a role for aberrant ion transport in the etiology of psychosis and provide a target for preemptive developmental interventions aimed at restoring the functional effect of this mutation.
Gesehen am 31.01.2020